KINERJA PEGAWAI KELURAHAN DALAM PENYALURAN BERAS PADA PROGRAM BERAS MISKIN DI KELURAHAN KAMPAL - Jamilah, Jamilah (Katalogis, 2018)
Based on the results of the study, that the Employee Performance At Village In Rice Distribution Program Rice Poor in Sub Kampal not yet effective, the First; aspects of productivity, ie employees village should also pay attention to giving understanding to the RTS-PM that Raskin was a government program for low-income people, so the RTS-PM has the right to scrutinize carefully the level of achievement indicators 6T, which is on target, right quantity, price, timely, quality, and proper administration. Second; Quality of Service, Many negative view formed on the organization of the public, comes as public dissatisfaction on the quality of service received from public organizations. Unfriendly attitude kelurahan staff in providing guidance to the RTS-PM very impressed unethical. Third; Responsiveness, The Village Kampal less facilitating the existence of poor people who do not have a card which is actually more worthy Raskin of Raskin recipients today. Employees village malpractice impressed only distribute Raskin, however, other problems inherent in raskin policies are rarely reported to the district level. Thus, the researchers conclude that the Village Employee Performance In Distribution of Rice In Rice Program Poor in Sub Kampal not maximized, because only two (2) aspects are fulfilled, namely the aspect of Responsibility and Accountability. While other aspects not maximized, namely the aspect of productivity, service quality and responsiveness.